Counseling on the Role and Function of Parole and Probation Office to the Community and Clients in the Garut Class II Parole and Probation Office (Ciamis Subdistrict) - Sasgin Azahra Damai; Aisyah; Reki Amaludin Akbal; Muhammad Ali Equatora (CV. Literasi Indonesia, 2023)
Correctional Centers become institutions in carrying out social guidance for Correctional Clients. The clients in the community environment require support from the community and other stakeholders. The parole and Probation Office as a system executor that required to be able to respond and anticipate various paradigm challenges that occur in the community. This community service activity is carried out to provide knowledge to the community about the role and functions of the Parole and Probation Office and to build communication between the Correctional Technical Implementation Unit and the community. The series of activities is filled with the implementation of socialization. The outcome of this activity is increasing public knowledge regarding the role and function of the Parole and Probation Office as an institution in implementing community guidance.